Immune-related potential biomarkers and therapeutic targets in coronary artery disease - Liu, Chaosheng; Liu, Jifeng; Zhang, Yunshu; Wang, Xi; Guan, Yue (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background: Coronary artery disease (CAD) is a complex illness with unknown pathophysiology. Peripheral biomarkers are a non-invasive method required to track the onset and progression of CAD and have unbeatable benefits in terms of early identification, prognostic assessment, and categorization of the diagnosis. This study aimed to identify and validate the diagnostic and therapeutic potential of differentially expressed immune-related genes (DE-IRGs) in CAD, which will aid in improving our knowledge on the etiology of CAD and in forming genetic predictions. Methods: First, we searched coronary heart disease in the Gene Expression Omnibus database and identified GSE20680 (CAD=87, Normal=52) as the trial set and GSE20681 (CAD=99, Normal=99) as the validation set. Functional enrichment analysis using protein-protein interactions, Gene Ontology, and Kyoto Encyclopedia of Genes and Genomes was carried out on the identified differentially expressed genes. Optimal feature genes (OFGs) were generated using the support vector machine recursive feature elimination algorithm and the least absolute shrinkage and selection operator algorithm. Furthermore, immune infiltration in CAD patients and healthy controls was compared using CIBERSORT, and the relationship between immune cells and OFGs was examined. In addition, we constructed potential targeted drugs for this model through the Drug-Gene Interaction database (DGIdb) database. Finally, we verify the expression of S100A8-dominated OFGs in the GSE20681 dataset to confirm the universality of our study.